Results of long-term antiviral prophylactic treatment on the course of herpes zoster ophthalmicus with ocular involvement: A case series in a tertiary uveitis clinic – A 1-year follow-up - Arash Maleki; Priya D. Patel; Amanda Colombo; C. Stephen Foster (Taiwan Journal of Ophthalmology)
PURPOSE: To study the efficacy of long-term antiviral monotherapy on herpes zoster ophthalmicus (HZO) with eye involvement. MATERIALS AND METHODS: The patients with primary, recurrent, and chronic HZO with at least 1 year of follow-up were included in the study. The primary endpoint of the study was HZO recurrence with ocular presentations. RESULTS: A total of 17 patients were included in the study. Eleven (64.7%) patients were included in the primary HZO group and 6 (35.3%) patients were included in the recurrent/chronic HZO group. In the primary HZO group, 10 (90.9%) patients responded to antiviral alone. One patient failed antiviral treatment after 7 months and responded to a combination of methotrexate and antiviral therapy. In the recurrent and chronic HZO group, 4 (66.7%) patients responded to isolated antiviral treatment. No systemic side effects were observed during the study period. CONCLUSION: Long-term antiviral monotherapy may be an effective prophylactic treatment in patients with primary, recurrent, persistent HZO to treat the infection and maintain remission; however, this hypothesis should be examined in more potent study with larger population.